Assessment of multidirectional movements of the common carotid artery in atherothrombotic stroke using dimensional speckle tracking carotid ultrasonography: A prospective, controlled cohort study. Issue 7 (30th March 2018) - Yoon, Ji Hyun; Han, Donghee; Kim, Sujin; Cho, In‐Jeong; Sung, Ji min; Lee, Jinyong; Ryoo, Hojin; Shim, Chi Young; Hong, Geu‐Ru; Chang, Hyuk‐Jae
Abstract : Aim: We aimed to explore the relevance of multidirectional movements of the common carotid artery in atherothrombotic stroke. Methods and Results: We prospectively enrolled 69 patients with atherothrombotic stroke (stroke group) and 69 age‐matched and sex‐matched controls (control group) who underwent carotid ultrasonography. Based on the speckle tracking technique, circumferential and radial movements of the common carotid artery were analyzed from transverse and longitudinal B‐mode images of the common carotid artery. Peak longitudinal and radial displacements, strain, and strain rate were measured. Mean age of the overall population was 64 ± 11 years, and 57% (78 patients) were men. In the transverse image, circumferential strain was significantly lower in the stroke group than in the control group (5.6 ± 1.6 vs 4.2 ± 1.7, P  <   .001). In multivariate logistic regression analysis, circumferential strain was independently associated with stroke (odds ratio: 0.60, P  =   .001). Compared with conventional risk factors, as well as carotid intima–media thickness and carotid plaque, the addition of a strain parameter appeared to improve discrimination of a stroke event (area under the receiver operating characteristic curve: 0.65 and 0.75 vs 0.84, respectively; P  <   .05 for both). Conclusions: Circumferential strain of the common carotid artery might serve as a novel surrogate marker of atherothrombotic stroke. Multidirectional strain imaging of the common carotid artery may provide more information than conventional carotid ultrasonography and identify clinical risk factors for risk stratification of an acute stroke event.